Work Life Balance Among Female School Teachers Delivering Online Curriculum in Bandgaon Block During COVID: a Empirical Study - Jayant Kumar Sahoo (PT FORMOSA CENDEKIA GLOBAL, 2023)
Work life balance today, in particular in instances of COVID the place home and work place have transgressed boundaries is an indispensable precursor for the well-being of an individual. A pleasurable job well-integrated into life, balances the usual intellectual and emotional quotient of working female especially in the modern pandemic in which the workplace is posing a new and not like set of challenges and troubles for women. Carrying on with on line lessons remotely has grow to be the order of the day, and it is turning into worrying when each school and personal life operate from the same space. The predominant idea here is to recognize challenges at some point of COVID which are being confronted with the aid of school teachers in Bandgaon block delivering content to students from home and their surviving strategies. A combination of 150 fermale teachers responses from primary, secondary and high school are covered in the study. Average literacy rate of Bandgaon Block in 2011 had been 54.46 in which, man and female literacy had been 69.02 and 39.95 respectively. Total literate in Bandgaon Block have been 805 of which man and woman have been 547 an 258 respectively. This study also identifies primary problems and challenges which confronted by unwedded and wedded working female in the course of Covid-19